Chemically modified biochar derived from effluent treatment plant sludge of a distillery for the removal of an emerging pollutant, tetracycline, from aqueous solution - Singh V.; Chakravarthi M.H.; Srivastava V.C. (My University, 2025)
Distilleries are among the most pollution-generating industries as their ≈80% raw material converted into waste. In the present study, sustainable biochar was prepared from distillery sludge (DS) by chemical activation with KOH, ZnCl2, and H3PO4 (coded as DS-K, DS-Z, DS-H) and used for the removal of tetracycline, an emerging pollutant. Additionally, biochar was also prepared by adding the distillery sludge and oily sludge from sugar mill in the ratio of 2:1 (coded as DS-O). The raw sludge and prepared biochar were characterized by various sophisticated techniques like XRF, XRD, TGA-FTIR, BET, FE-SEM, and zeta potential analyzer. FTIR, coupled with the TGA system, gave traces of CO2 and H2O (steam) as the temperature of the sample increased. Batch adsorption study showed TC removal efficiencies of 57%, 64%, 43%, and 70% by DS-K, DS-Z, DS-H, and DS-O, respectively, at optimum conditions: Co = 20 mg L−1, time = 300 min, rpm = 160 ± 5, dose = 1 g L−1, T = 25 ±1 °C, and pH = 6. Experimental data was well-fitted in both pseudo-first-order and pseudo-second-order kinetic models. Langmuir isotherm nicely described the adsorption of TC onto biochar. pH played a significant role in the adsorption due to the amphoteric behavior of TC. Reusability studies showed a marginal decrease in removal efficiencies of ≈ 9%, ≈ 7%, ≈ 4%, and ≈ 8% after three consecutive runs with DS-O, DS-Z, DS-K, and DS-H, respectively. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.